HEMODYNAMIC FEATURES OF PRELOADING AND COLOADING FLUIDS IN PATIENTS UNDER SPINAL ANESTHESIA AT EMANUEL HOSPITAL BANJARNEGARA - Apriliyanti, Risni; Suandika, Made; Susanto, Amin (Jurnal Ilmiah Wahana Pendidikan, 2024)
Background: Spinal anesthesia techniques can cause acute vasodilation due to sympathetic nerve blockade, resulting in decreased hemodynamics in spinal anesthesia patients. Central blood volume can be increased to prevent hemodynamic decline by administering fluid preloading and coloading. The aim of this study was to determine the hemodynamic status of preloading and coloading fluids in spinal anesthesia patients at Emanuel Banjarnegara Hospital. Method: The research design used is descriptive with a cross-sectional approach. This research was conducted in May 2023. Samples were taken using a purposive sampling technique as many as 37 respondents who met the inclusion criteria. The instruments used in this study were observation sheets and bedsite monitors. Data processing techniques in this study using univariate analysis. Results: The results showed that the majority of patients in this study experienced normal preloading hemodynamics, blood pressure with 23 (62.2%) respondents, normal pulse for 32 (86.5%) respondents, normal MAP for 31 (83.8%) respondents, normal temperature. 37 (100%) respondents, normal RR 37 (100%) respondents, normal SpO2 37 (100%) respondents. Hemodynamic coloading blood pressure was normal with 25 (67.6%) respondents, normal pulse with 30 (81.1%) respondents, normal MAP with 27 (73%) respondents, normal temperature with 37 (100%) respondents, normal RR with 37 (100%) respondents, normal SpO2 37(100%) respondents. Conclusion: Giving preloading and coloading fluids can maintain hemodynamic status in spinal anesthesia patients at Emanuel Banjarnegara Hospital.